Coupling mitogenesis and mitophagy for longevity - Palikaras, K.; Lionaki, E.; Tavernarakis, N. (Autophagy, 2015)
Maintenance of mitochondrial function and energy homeostasis requires both generation of newly synthesized and elimination of dysfunctional mitochondria. Impaired mitochondrial function and excessive mitochondrial content are major characteristics of aging and several human pathophysiological conditions, highlighting the pivotal role of the coordination between mitochondrial biogenesis and mitophagy. However, the cellular and molecular underpinnings of mitochondrial mass homeostasis remain obscure. In our recent study, we demonstrate that DCT-1, the Caenorhabditis elegans homolog of mammalian BNIP3 and BNIP3L/NIX, is a key mediator of mitophagy promoting longevity under stress. DCT-1 acts downstream of the PINK-1-PDR-1/Parkin pathway and is ubiquitinated upon mitophagy-inducing conditions to mediate the removal of damaged mitochondria. Accumulation of damaged mitochondria triggers SKN-1 activation, which initiates a bipartite retrograde signaling pathway stimulating the coordinated induction of both mitochondrial biogenesis and mitophagy genes. Taken together, our results unravel a homeostatic feedback loop that allows cells to adjust their mitochondrial population in response to environmental and intracellular cues. Age-dependent decline of mitophagy both inhibits removal of dysfunctional or superfluous mitochondria and impairs mitochondrial biogenesis resulting in progressive mitochondrial accretion and consequently, deterioration of cell function.
Palikaras, KonstantinosLionaki, EiriniTavernarakis, NektariosengResearch Support, Non-U.S. Gov'tAutophagy. 2015;11(8):1428-30. doi: 10.1080/15548627.2015.1061172.
Keywords: *Autophagy; *Mitophagy; Aging; Aging/*metabolism; Animals; Autophagy; Caenorhabditis elegans; Caenorhabditis elegans Proteins/metabolism; Caenorhabditis elegans/*physiology; Carrier Proteins; DNA-Binding Proteins/metabolism; homeostasis; Longevity; Membrane Proteins/metabolism; Mitochondria; Mitochondria/*metabolism; mitophagy; signal transduction; stress; Transcription Factors/metabolism